2017
DOI: 10.1051/e3sconf/20172200156
|View full text |Cite
|
Sign up to set email alerts
|

Optimization for energy efficiency of underground building envelope thermal performance in different climate zones of China

Abstract: Abstract. The object of this article is to investigate the influence of thermal performance of envelopes in shallow-buried buildings on energy consumption for different climate zones of China. For the purpose of this study, an effective building energy simulation tool (DeST) developed by Tsinghua University was chosen to model the heat transfer in underground buildings. Based on the simulative results, energy consumption for heating and cooling for the whole year was obtained. The results showed that the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It was found that the usage of underground construction in hot climates should be encouraged since natural ventilation and daylight can reduce summer temperatures by 3 degrees Celsius and evaporative cooling can cool the indoor environment by roughly 12 degrees Celsius [21]. Although, there is a finding revealed that the connection between energy consumption and U-value of envelopes for underground constructions differs from that for above-ground buildings: enhancing thermal performance of outside walls does not reduce energy consumption and may even increase energy costs [22]. The thermal comfort survey results revealed a neutral temperature of 28°C and a comfort-temperature range of 25°C to 30°C for occupants of Yazd's traditional central-courtyard houses.…”
Section: Basementmentioning
confidence: 99%
“…It was found that the usage of underground construction in hot climates should be encouraged since natural ventilation and daylight can reduce summer temperatures by 3 degrees Celsius and evaporative cooling can cool the indoor environment by roughly 12 degrees Celsius [21]. Although, there is a finding revealed that the connection between energy consumption and U-value of envelopes for underground constructions differs from that for above-ground buildings: enhancing thermal performance of outside walls does not reduce energy consumption and may even increase energy costs [22]. The thermal comfort survey results revealed a neutral temperature of 28°C and a comfort-temperature range of 25°C to 30°C for occupants of Yazd's traditional central-courtyard houses.…”
Section: Basementmentioning
confidence: 99%
“…In the context of insulation, Shi et al [12] investigated the influence of thermal performance of envelopes on energy consumption in underground buildings in different climate zones of China. The results indicated that the relationship between the energy consumption and the thermal transmittances of envelopes for underground buildings is different with those for aboveground buildings.…”
Section: Building Envelopementioning
confidence: 99%